Metformin activates a duodenal Ampk-dependent pathway to lower hepatic glucose production in rats - Duca,FA; Cote,CD; Rasmussen,BA; Zadeh-Tahmasebi,M; Rutter,GA; Filippi,BM; Lam,TKT (Nature Medicine, 2015)
Metformin is a first-line therapeutic option for the treatment of type 2 diabetes, even though its underlying mechanisms of action are relatively unclear1,2,3,4,5,6. Metformin lowers blood glucose levels by inhibiting hepatic glucose production (HGP), an effect originally postulated to be due to a hepatic AMP-activated protein kinase (AMPK)-dependent mechanism5,6. However, studies have questioned the contribution of hepatic AMPK to the effects of metformin on lowering hyperglycemia1,3,4, and a gut–brain–liver axis that mediates intestinal nutrient- and hormone-induced lowering of HGP has been identified7. Thus, it is possible that metformin affects HGP through this inter-organ crosstalk. Here we show that intraduodenal infusion of metformin for 50 min activated duodenal mucosal Ampk and lowered HGP in a rat 3 d high fat diet (HFD)-induced model of insulin resistance. Inhibition of duodenal Ampk negated the HGP-lowering effect of intraduodenal metformin, and both duodenal glucagon-like peptide-1 receptor (Glp-1r)–protein kinase A (Pka) signaling and a neuronal-mediated gut–brain–liver pathway were required for metformin to lower HGP. Preabsorptive metformin also lowered HGP in rat models of 28 d HFD–induced obesity and insulin resistance and nicotinamide (NA)–streptozotocin (STZ)–HFD-induced type 2 diabetes. In an unclamped setting, inhibition of duodenal Ampk reduced the glucose-lowering effects of a bolus metformin treatment in rat models of diabetes. These findings show that, in rat models of both obesity and diabetes, metformin activates a previously unappreciated duodenal Ampk–dependent pathway to lower HGP and plasma glucose levels.